Salome Gluecksohn-Waelsch. 6 October 1907—7 November 2007. (14th December 2019) - Papaioannou, Virginia E.
Abstract : Salome Gluecksohn-Waelsch was a pioneer in establishing the field of mammalian developmental genetics, bringing together experimental embryology and genetics at a time when the role of genes in development was far from accepted. She studied in Germany in the 1930s with the renowned experimental embryologist Hans Spemann and then moved to New York City where she spent her entire professional career at Columbia University and the Albert Einstein College of Medicine of Yeshiva University. Her career was remarkable not only for its longevity—she continued experiments well into her 90s—but also for ushering in new ways of approaching developmental biology in mammals. In her studies of the T -complex in mice, she made use of naturally occurring mutations as nature's own experiments that allowed the investigation of the normal role of the genes in the events of morphogenesis. In her later work with the albino chromosomal deletions, she extended her studies to the genetics of physiological traits. Throughout the decades that saw a blossoming of the entire field of genetics, Salome Gluecksohn-Waelsch's work tackling some of the most perplexing problems in mammalian genetics firmly established the mouse as model organism, not only for studying development, but also for the eventual application of molecular biology techniques to development. Her published work is a beautifully coherent and rigorous opus, for which she received many honours. Her influence on a generation of geneticists, developmental biologists and the field of developmental genetics was profound. The life of Salome Gluecksohn–Waelsch spanned a century that suffered the destructive upheaval of two world wars but also saw phenomenal progress in the sciences, including embryology and genetics. At the start of Salome's career, these two fields were far apart and developmental genetics was barely a concept. Along with a few other pioneers, Salome was instrumental in establishing that genes actually had roles in development and in founding the field of mammalian developmental genetics. Her career laid the ground work for the eventual integration of genetic and developmental studies through molecular biology. Salome Gluecksohn–Waelsch published under four different names at different stages of her life and career: Salome Glücksohn, Salome Gluecksohn–Schoenheimer, Salome Gluecksohn–Waelsch, and Salome G. Waelsch. Among her colleagues and friends, she was almost universally known as Salome and so for the purpose of this biographical memoir, I have chosen to refer to her by her first name, out of friendship and respect.